Prevalence and antimicrobial sensitivity pattern of urinary tract infection among children with cerebral palsy, Moshi, Tanzania - Ryakitimbo A; Philemon R; Mazuguni F; Msuya L (Dove Medical Press, 2018)
Amon Ryakitimbo,1 Rune Philemon,1,2 Festo Mazuguni,3 Levina Msuya1,2 1Department of Pediatric and Child Health, Kilimanjaro Christian Medical University College, Moshi, Tanzania; 2Department of Pediatric and Child Health, Kilimanjaro Christian Medical Centre, Moshi, Tanzania; 3Department of Epidemiology and Applied Biostatistics, Institute of Public Health, Kilimanjaro Christian Medical University College, Moshi, Tanzania Background: Urinary tract infection (UTI) in children with cerebral palsy (CP) is a challenging yet common clinical condition. Children with CP bare the greatest risk of contracting UTI because of their difficulties in neuromotor control which lead to delay of bladder control, causing incomplete bladder emptying and urine retention. Method: This was an analytical cross-sectional study that was conducted from September 2016 to March 2017 at Comprehensive Community Based Rehabilitation in Tanzania – Moshi and Kilimanjaro Christian Medical Centre Neurological Pediatrics Outpatient Clinic. All children who met the inclusion criteria were studied. Urine samples were collected at one point by catheterization, and urine dipstick and urine culture were done. Data were analyzed using SPSS version 20. Results: A total of 99 children were enrolled in the study. The median age was 4 years (3–8 years); 53.5% were aged between 2 and 4 years. More than half were male. UTI was detected in 13.1% (n=13) of the children. Five causative agents of UTI were isolated, namely Escherichia coli, Proteus mirabilis, Klebsiella pneumonia, Staphylococcus aureus, and Enterococcus faecalis. The two most common organisms, E. coli and P. mirabilis, both had low sensitivity to ampicillin and co-trimoxazole while they were sensitive to ciprofloxacin and ceftriaxone. Conclusion: UTI is a common finding among children with CP. E. coli and P. mirabilis are the commonest causative agents and are sensitive to ciprofloxacin and ceftriaxone but have low sensitivity to ampicillin and co-trimoxazole. Keywords: urinary tract infection, cerebral palsy, Moshi, Tanzania